Efektivitas Teknik Empty Chair Dalam Layanan Bimbingan Konseling Untuk Rehabilitasi Korban Bullyinging - Hidroar, Alensio Nico Nico; Muhid, Abdul (Counseling AS SYAMIL: Jurnal Ilmiah Bimbingan Konseling Islam, 2022)
Abstract: Bullying in children can happen anywhere and anytime, including at school. In modern times like this, bullying also occurs through social media now that pursues violence. Forms of bullying can occur in physical, verbal, and mental forms. Bullying behavior can cause fear for the victim, because it is done continuously. Bullying behavior has an impact on psychological well-being. decline and poor social adjustment, namely negative emotions are more likely to be felt, such as anger, hatred, urgency, disappointment, not getting comfort, feeling depressed but unable to fight it, and affecting the academic achievement of students because it is difficult to adjust to their environment. The purpose of this study was to determine the effectiveness of the empty chair technique in counseling guidance services for the rehabilitation of bullying victims. By using qualitative research methods. Where the data obtained from the results of literature review (literature review). The results show that counseling therapy using the empty chair technique has proven to be effective as rehabilitation for bullying victims. Keywords: Bullying, Empty Chair Counseling, Rehabilitation